Publisher Correction: Dimethyl fumarate and 4-octyl itaconate are anticoagulants that suppress Tissue Factor in macrophages via inhibition of Type I Interferon (Nature Communications, (2023), 14, 1, (3513), 10.1038/s41467-023-39174-1) - Mills, Kingston; Ni Cheallaigh, Cliona; O'Neill, Luke; Mc Loughlin, Rachel (My University, 2023)
The original version of this Article contained an error in the spelling of the surname for the author Luke A J O’Neill, which was incorrectly given as ‘O’ Neill’ with an additional space. This has now been corrected in both the PDF and HTML versions of the Article.
PUBLISHED
cited By 0
Keywords: correction; Dimethyl fumarate; Tissue; Mikkelsen-; Dimethyl fumarate; Tissue